2014
DOI: 10.5959/eimj.v6i3.233
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Students’ Perception of their Educational Environment: A study to identify the areas of concern for remedial measures at two Schools of Physiotherapy in Malaysia.

Abstract: Introduction: In order to produce competent physiotherapy graduates with the generic attributes much sought after by the health care providers in the country, the higher education institution needs to ensure the educational environment of the school is positive. Students' positive perception of their educational environment would facilitate their learning experience to be more meaningful and relevant. Objective: The aim of this study was to measure physiotherapy students' perception of their educational enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…For instance, in one of the institutions, the College of Medicine at King Saud University, Saudi Arabia, the curriculum was reported as overcrowded and teacher centred. [11] However, the score found in the current study was lower than those found in Nigeria (131/200), [10] Malaysia (133/200), [9] Sri Lanka (141/200) [16] and Sweden (150/200). [2] This may reflect that these institutions are fairly innovative in terms of providing a studentcentred approach to education, [17] and the physiotherapy lecturers at UR should explore how they can learn from good practices in those countries.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…For instance, in one of the institutions, the College of Medicine at King Saud University, Saudi Arabia, the curriculum was reported as overcrowded and teacher centred. [11] However, the score found in the current study was lower than those found in Nigeria (131/200), [10] Malaysia (133/200), [9] Sri Lanka (141/200) [16] and Sweden (150/200). [2] This may reflect that these institutions are fairly innovative in terms of providing a studentcentred approach to education, [17] and the physiotherapy lecturers at UR should explore how they can learn from good practices in those countries.…”
Section: Discussioncontrasting
confidence: 70%
“…It is not appropriate to fully compare this study with others, because of contextual dissimilarities and different sample sizes used. However, while contrasting and interpreting the scores against the guidelines proposed by the developers of the DREEM instrument, it emerged that this study has a common main finding with other similar studies conducted elsewhere, such as in India, [8] Malaysia, [9] Nigeria [10] and Sweden, [2] for example. All these studies reported that students view their EE in general as more positive than negative, thereby having an optimistic view of their learning situation, lecturers, educational atmosphere and academic and social life.…”
Section: Discussionmentioning
confidence: 55%
“…The rating of the EE as ‘more positive than negative’ found in this sample is similar to what has been reported in other studies evaluating physical therapy programs [2,4,12,17,18]; however, we obtained lower values for the total mean score (120.9), which could have been due to the low scores of the perception of learning and social perceptions subscales affecting the total mean score, similar to the findings of Odole et al [4]. These findings are similar to the scores obtained by Sunkad et al [17], who evaluated health care programs and found that physical therapy had the lowest scores.…”
Section: Discussionsupporting
confidence: 90%
“…The problem areas identified in this study are similar to those found in other physical therapy programs, including a teaching-centered approach that overemphasizes memorization, stress or fatigue due an overloaded curriculum and lack of information about mental health support, and cheating in the program due an overloaded curriculum [2,4,10,12,18], and these factors must be taken into account in the evaluation of the new curriculum of the program.…”
Section: Discussionmentioning
confidence: 67%
“…Physiotherapy students' perceptions regarding their learning environment has shown to be of great importance, since it might have an effect on the academic performances. Such study was done in Malaysia and results showed that students had positive perception towards their educational environment (Veasuvalingam and Arzuman, 2014). However, campus experience also matters as it is in fact the actual happening around students' and their studies.…”
Section: Study Backgroundmentioning
confidence: 99%